Psikologi layanan terhadap pemustaka dan kualitas layanan prima - Faridah Hanum (UIN Sumatera Utara, 2017)
This article discusses about service psychology of users and quality of service excellence. Service or user psychology is a science that studies human behavior in the process of interaction work in service centers, that is between customers/ users and officers/ employees. Keywords: psychology, service, users